Research on Global Dispatching Technology for Fully Automatic Operation System Based on Interconnection Technology - LIU Long; WANG Yeliu; REN Ying; LI Denggen; ZHANG Datao (Kongzhi Yu Xinxi Jishu)
Under the guidance of the Outline for the Development of Smart Urban Rail Transit in China, the technologies of interconnection, fully automatic operation (FAO), and intelligent transportation organization have shaped the development trends in the Chinese urban rail transit sector. This paper proposes an interconnection-based global dispatching technical solution for FAO systems, drawing on an analysis of relevant interconnection techniques. The objective is to develop a global dispatching system over networked rail transit lines based on cloud platforms, to tackle increasingly prominent issues in networked operational scenarios, such as rising operating costs and inconvenient passenger transfer. Firstly, the key technical routes for interconnection in FAO were reviewed. Then, a global dispatching solution was devised based on networked rail transit lines, including the relevant system architecture and a multi-objective optimization model. Finally, based on the operational and passenger flow data from a city's rail transit network, the multi-objective optimization model for the proposed dispatching solution was simulated for verification using a genetic algorithm. Simulation results showed that the application of this solution effectively reduced the total social consumption cost by 10.8% and shortened passenger travel time by 12%.